Reduced Hyperpolarization-Activated Current Contributes to Enhanced Intrinsic Excitability in Cultured Hippocampal Neurons from PrP−/− Mice - Fan, Jing; Stemkowski, Patrick L.; Gandini, Maria A.; Black, Stefanie A.; Zhang, Zizhen; Souza, Ivana A.; Chen, Lina; Zamponi, Gerald W. (Frontiers in Cellular Neuroscience, 2016)
Genetic ablation of cellular prion protein (PrPC) has been linked to increased neuronal excitability and synaptic activity in the hippocampus. We have previously shown that synaptic activity in hippocampi of PrP-null mice is increased due to enhanced N-methyl-D-aspartate receptor (NMDAR) function. Here, we focused on the effect of PRNP gene knock-out (KO) on intrinsic neuronal excitability, and in particular, the underlying ionic mechanism in hippocampal neurons cultured from P0 mouse pups. We found that the absence of PrPC profoundly affected the firing properties of cultured hippocampal neurons in the presence of synaptic blockers. The membrane impedance was greater in PrP-null neurons, and this difference was abolished by the hyperpolarization-activated cyclic nucleotide-gated (HCN) channel blocker ZD7288 (100 µM). HCN channel activity appeared to be functionally regulated by PrPC. The amplitude of voltage sag, a characteristic of activating HCN channel current (Ih), was decreased in null mice. Moreover, Ih peak current was reduced, along with a hyperpolarizing shift in activation gating and slower kinetics. However, neither HCN1 nor HCN2 formed a biochemical complex with PrPC. These results suggest that the absence of PrP downregulates the activity of HCN channels through activation of a cell signaling pathway rather than through direct interactions. This in turn contributes to an increase in membrane impedance to potentiate neuronal excitability.